Lipid Profile and Urinary Protein a Creatinine Ratio Changes in Pre-Eclampsia Cases in and Around Chitradurga (Global Journal of Medical Research, 2014)
Abstract not found
Keywords: preeclampsia; urinary protein; urinary creatinine; urinary protein: creatinine ratio; serum lipid profile